Trypsin and Chymotrypsin Usage in Reduction of Pain Following the Surgical Extraction of Mandibular Third Molars - G, HARINI; PRABU, DR. DINESH; R N, DR. BALAKRISHNAN (The journal of contemporary issues in business and government, 2021)
The aim of the article is to evaluate the effect of trypsin and chymotrypsin (proteolytic enzyme ) on pain and swelling after the surgical removal of mandibular third molar. A prospective randomised clinical study was conducted among 30 patients requiring the surgical removal of impacted mandibular third molars. All the impacted molars were surgically removed and the patients were administered trypsin and chymotrypsin orally along with amoxicillin. The postoperative pain was assessed on 3rd and 7th consecutive days after extraction. 30 patients requiring the extraction of mandibular third molars were taken in this study.16 patients are male and 14 patients are females. There was the reduction in pain post operatively. The comparison was taken between 3rd and 7th postoperative days. Chymoral Forte can be used as a successful oral enzyme therapy for oral surgery patients, especially after the removal of impacted third molars.